2009
DOI: 10.1016/j.bpj.2009.07.059
|View full text |Cite
|
Sign up to set email alerts
|

Homo-FRET Imaging Enables Quantification of Protein Cluster Sizes with Subcellular Resolution

Abstract: Fluorescence-anisotropy-based homo-FRET detection methods can be employed to study clustering of identical proteins in cells. Here, the potential of fluorescence anisotropy microscopy for the quantitative imaging of protein clusters with subcellular resolution is investigated. Steady-state and time-resolved anisotropy detection and both one- and two-photon excitation methods are compared. The methods are evaluated on cells expressing green fluorescent protein (GFP) constructs that contain one or two FK506-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
174
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(184 citation statements)
references
References 27 publications
(53 reference statements)
8
174
0
Order By: Relevance
“…Our observation that only a subset of BRI1-SERK3 heterooligomers is present after ligand depletion is comparable to findings for EGFR in mammalian cells, as demonstrated by Bader et al (2009). Notably, for bone morphogenic protein receptors, differential signaling responses (Nohe et al, 2002) and endocytic routes (Hartung et al, 2006) for preformed and ligand-induced receptor complexes were observed.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our observation that only a subset of BRI1-SERK3 heterooligomers is present after ligand depletion is comparable to findings for EGFR in mammalian cells, as demonstrated by Bader et al (2009). Notably, for bone morphogenic protein receptors, differential signaling responses (Nohe et al, 2002) and endocytic routes (Hartung et al, 2006) for preformed and ligand-induced receptor complexes were observed.…”
Section: Discussionsupporting
confidence: 84%
“…promote lateral signal propagation (Martin-Fernandez et al, 2002;Yu et al, 2002;Bader et al, 2009). Our observation that only a subset of BRI1-SERK3 heterooligomers is present after ligand depletion is comparable to findings for EGFR in mammalian cells, as demonstrated by Bader et al (2009).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…However, the different techniques, cell types, and conditions of the experiments have resulted in conflicting and contradictory results. Several studies using fixed cells and/or low temperature incubations based on hetero-or homo-FRET have indicated that <10% to as much as 50% of ErbB1 may exist as preformed dimers or oligomers (17,19,20). Inhibition of the tyrosine kinase activity of the receptor led to disaggregation of the transient dimers and clusters to monomers (18), suggesting that some measurements may have been made on nonstarved cells with preactivated receptors.…”
mentioning
confidence: 99%